Cognitive impairment is not a predictor of failure to adhere to anticoagulation of stroke patients with atrial fibrillation - Horstmann, Solveig; Rizos, Timolaos; Saribas, Michaela; Efthymiou, Evdokia; Rauch, Geraldine; Veltkamp, Roland (Cerebrovascular diseases, 2015)
Background: Oral anticoagulation (OAC) with vitamin K antagonists (VKA) or direct oral anticoagulants (DOAC) is an effective strategy that is used for stroke prevention in patients with atrial fibrillation (AF). However, OAC is underused particularly in elderly patients, who are often physically disabled or cognitively impaired. We aimed at evaluating the effect of cognitive status and disability on OAC adherence 1 year after stroke or TIA. Methods: In this prospective, single-center, observational study patients with ischemic stroke or TIA were consecutively included between 3/2011 and 9/2012. The detailed medical history, basic demographic variables, cardiovascular risk factors, stroke severity according to the National Institutes of Health Stroke Scale (NIHSS), medication including OAC were all recorded. Cognitive performance was measured using the Montreal Cognitive Assessment (MoCA) score at baseline. The functional status was assessed by recording activities and instrumental activities of daily living, respectively (ADL, IADL). After 12 months, patients had a follow-up visit to reassess the cognitive and functional status (MoCA, ADL and IADL) and to document the current use of OAC. Results: In total, 12 months after the ischemic stroke or TIA AF had been diagnosed in 160/586 (27.3%). Of these, 151 patients (94.4%) were treated with OAC. OAC was performed using VKA in 79/151 (52.3%) and DOACs in 72/151 (47.7%). Cognitive impairment at 12 months follow-up was not associated with the absence of OAC treatment. However, regression analysis revealed that patients with AF with physical (ADL) and functional disability (IADL) were less likely to be treated with OAC (p = 0.08 and p = 0.04, respectively) 12 months after a stroke. None of these two factors, however, was independently associated with nonadherence to OAC 12 months after stroke. Although cognitive performance was similar in patients receiving VKA and direct anticoagulants (DOAC), adherence to VKA tended to be lower (82.6 vs. 94.6%, p = 0.12). Conclusions: In stroke and TIA patients with AF, the multifactorial medical and functional constellation rather than cognitive impairment specifically can be an obstacle for long-term OAC.